Influence of Adherence to Leave Policies on Teachers’ Performance In Public Secondary Schools In Homa-Bay County (International Journal of Scientific Research and Management (IJSRM), 2021)
The provision of paid leave and time-offs are practices in human resource administration that aims at reducing burnout, stress as well as family-work conflict. Thus, provision of leave allows an employee to recuperate from the daily pressure of work. However, in the education sector in Kenya, information concerning administration of leave policies to teachers is not clear. In some counties such as Homa Bay in Kenya, secondary school teachers are faced with problems such lesson overload, inadequate time-offs for sick and lactating teachers, and inadequate bereavement leaves. The number of teachers seeking for transfer has also increased over the years. The purpose of this study was to analyse the influence of adherence to leave policies by school administration on performance of teachers in public secondary schools in Homa Bay County. Specific objectives were to determine the level of teachers’ performance and to establish the influence of provision of leave on performance of teachers. The study employed descriptive survey design. Target population comprised a total of 257 principals and 2,231 teachers. Yamane’s formula was used to calculate 292 teachers and 22 Principals from whom data was collected using questionnaire and interview schedule respectively. The study found that adherence to leave policies (F = 66.488 ; P = 0.0) as a significant predictor of teachers’ performance abeit with a low contribution (21.8% or R2 =0.218) change in teacher performance. It is concluded that adherence to leave policies do not provide adequate satisfaction to elicit effort towards enhanced performance among secondary school teacher.